Pterostilbene Alleviates Chlorpyrifos-Induced Damage During Porcine Oocyte Maturation - Guo, Lili; Zhao, Yongda; Huan, Yanjun (Frontiers in Cell and Developmental Biology, 2021)
Chlorpyrifos (CPF), a widely used organophosphate pesticide, is reported to severely impair mammalian reproductive system. Pterostilbene (PTS), an effective free radical scavenger, is considered as beneficial for mammalian reproduction. However, the toxicity of CPF on oocyte maturation and whether PTS can eliminate the detrimental effect of CPF on oocytes remain unclear. Here, porcine oocytes were applied to investigate the potential effect and possible mechanism of CPF and PTS during oocyte maturation. This work demonstrated that CPF significantly delayed the meiotic progression and decreased the polar body extrusion by disturbing spindle assembly and chromosome alignment and causing DNA damage in oocytes (P<0.05). And, CPF significantly impaired oocyte cytoplasmic maturation by inducing the high level of reactive oxygen species and decreasing glutathione content (P<0.05). Moreover, CPF significantly triggered embryo apoptosis and reduced the blastocyst rate and cell number following parthenogenetic activation (P<0.05). Whereas CPF-exposed oocytes were treated with PTS, these defects caused by CPF were obviously rescued, and oocyte maturation and subsequent embryonic development were also significantly ameliorated (P<0.05). In conclusion, these results revealed that CPF exerted the toxic effect on porcine oocytes, while PTS effectively alleviated CPF-induced damage on oocytes. This work provides a potential strategy to protect oocyte maturation in mammalian species.